Characterization of host substrates of SARS-CoV-2 main protease - Melano, Ivonne; Lo, Yan-Chung; Su, Wen-Chi (Frontiers in Microbiology, 2023)
The main protease (Mpro) plays a crucial role in coronavirus, as it cleaves viral polyproteins and host cellular proteins to ensure successful replication. In this review, we discuss the preference in the recognition sequence of Mpro based on sequence-based studies and structural information and highlight the recent advances in computational and experimental approaches that have aided in discovering novel Mpro substrates. In addition, we provide an overview of the current understanding of Mpro host substrates and their implications for viral replication and pathogenesis. As Mpro has emerged as a promising target for the development of antiviral drugs, further insight into its substrate specificity may contribute to the design of specific inhibitors.